Исследование спектра высокого разрешения полосы v2+v10 молекулы 13C2H4; Известия вузов. Физика; Т. 59, № 9 - Онопенко Г. А. Галина Александровна; Моржикова Ю. Б. Юлия Борисовна; Зятькова А. Г. Анастасия Георгиевна; Замотаева В. А. Валерия Александровна; Буттерсак Т. Тильман (2016, 2016)
Заглавие с экрана